Survei Terhadap Pengukuran Kesamaan Teks: Survey of Text Similarity Measurement - Musodo, Krisna Adiyarta; Suwasti Broto (DRPM Universitas Budi Luhur, 2021)
Measuring the similarity between words, sentences, paragraphs and documents is an important research and discussion space in various discussions such as information search, document grouping, word-sense disambiguation, automatic essay scoring, short answer assessment, machine translation and text summarization. This article discus a survey which discussing methods for measuring the similarity of text or strings. This article is structred into three approaches; String-based, corpus-based, and knowledge-based similarity measures and presents the combinations of these similarities measures.